Criminal Clear Statement Rules - Carissa Byrne Hessick; Joseph E. Kennedy (Washington University Law Review, 2019)
There is a broad consensus in the criminal justice community that our criminal statutes are a mess: They are imprecise, overly broad, and overly punitive. Legislatures write these laws because there are significant political incentives for them to be “tough on crime” and few incentives for them to write carefully crafted laws. The problems of over-criminalization thus seem to be both a predictable yet intractable consequence of the incentives that legislatures face. But this Article offers a novel solution: Judges should develop new clear statement rules to interpret criminal statutes. The Supreme Court has created clear statement rules to protect important values, such as federalism and the separation of powers. Legislatures can overcome those values, but only if they do so affirmatively and unambiguously. Just as existing clear statement rules protect important structural values, new criminal clear statement rules would protect important criminal justice values. Unless statutes clearly state that they reject those values, clear statement rules will result in statutory interpretations that better protect the interests of criminal defendants. The result will be clearer and more thoughtful criminal laws—both because legislatures will write better statutes and because judges will construe poorly drafted statutes in a more narrow and predictable manner. In addition to making the case for criminal clear statement rules as a general interpretive tool, this Article proposes two specific clear statement rules. One rule would create a default presumption of a knowing mental state requirement for material elements. The other would impose a substantial harm requirement. Both would markedly improve the state of modern criminal law.
Keywords: Clear statement rule; Criminal law; Mens rea; Substantial harm; Statutory interpretation; Legislative dysfunction; Over-criminalization